Guías para la transfusión de sangre y sus componentes Guidelines for the transfusion of blood and its components - Mauricio Salazar (Pan American Health Organization, 2003)
There is no general consensus on the appropriate use of blood and its components. The resulting lack of transfusion guidelines is a weakness in our hospitals and health centers that directly affects good transfusion practice. Based on a literature review, this piece offers some general guidelines on the appropriate use of transfusion therapy. These guidelines can serve as the basis for preparing more-specific guides that take into account the individual needs of each hospital center.